Characterizing Solution for Stock Portfolio Problem via Pythagorean Fuzzy Approach - Hamiden Abd El-Wahed Khalifa (Environmental Energy and Economic Research, 2020)
The portfolio optimization is one of the fundamental problems in asset management that aims to reduce the risk of an investment by diversifying it into assets expected to fluctuate independently. A portfolio is a grouping of financial assets such as stocks, bonds, commodities, currencies and cash equivalents, as well as their funds counterparts, including mutual, exchange- traded and closed funds. A portfolio can also consist of non-publicly tradable securities, like real estate, art, and private investment. This paper aims to study stock portfolio investment problem with pythagorean fuzzy numbers. After converting the problem into the corresponding crisp based on the score function, a solution procedure is suggested to give the decision of the portfolio investment combined with investors in savings and securities. The advantages of this study are: The investor is freely to choose the risk coefficients enable him/ her to maximize the expected returns; also he may determine his/ her strategies under consideration of his/ her own conditions. An example is introduce to clarify the practically and the efficiency of the technique.